Aplication of Appropriate Fertilizer Spreader Technology to Increase the Productivity of Tobbaco Farmers in Condongcampur Village, Kebumen - Farhani, Khansa Anggraeta; Khasanah, Okti Nurul; Rizki, Rizki; Nadi, Danu Tirta; Oktaviani, Okta; Arrois, Alief Barrun; Hakim, Fahmi Azizul; Khodijah, Khoiriyah; Hanun, Nadia Rizka; Susanti, Laely; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This Community Service (Abdimas) activity is an integral part of the Muhammadiyah University of Purwokerto’s Community Service Program (KKN) and is being held in Condongcampur Village, Sruweng District, Kebumen Regency. The village is known as one of Kebumen’s tobacco-producing areas. However, local farmers still face challenges in the fertilization process, particularly in terms of the effectiveness and efficiency of fertilizer distribution. Most large-scale farmers still use manual methods, which are not only time-consuming and labor-intensive but also ineffective in delivering fertilizer. To address these issues, the KKN team proposed a solution in the form of a simple fertilizer spreader. This activity employed a participatory, app-based approach. This approach aligns with the program’s mission: to help increase agricultural yields through the use of appropriate technology, particularly in the planting and fertilization processes. The results of the activity showed that the use of the fertilizer spreader increased work efficiency by up to 40%, distributed fertilizer more evenly and measurably, and reduced the physical burden on farmers. The response from the farmers was very positive, as evidenced by their enthusiasm for using the tool. This simple innovation is expected to be a long-term solution to support increased tobacco productivity in Condongcampur Village, while also encouraging farmer independence through the use of technology that suits their needs